2021
DOI: 10.1155/2021/6474706
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of the Wound Healing Effect of a Novel Topical Cream Formula Based on Ginkgo biloba Extract on Wounds in Diabetic Rats

Abstract: Despite advances in diabetes care, impaired diabetic wound healing remains a significant clinical problem. The present study was aimed at developing a novel cream based on Ginkgo biloba extract and investigating its wound healing effect on full-thickness wounds in diabetic rats. The topical formulated oil-in-water emulsion-based cream contains Ginkgo biloba aqueous extract in an amount of about 1% to 5% as an active agent. The prepared formula was subjected to physicochemical assessment and pharmacotechnical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
(49 reference statements)
3
13
0
Order By: Relevance
“…In the present study, topical application of GKNG showed better antioxidant property than the GK gel and SA gel and showed improved wound healing potential. The findings were consistent with the previously published reports [ 9 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In the present study, topical application of GKNG showed better antioxidant property than the GK gel and SA gel and showed improved wound healing potential. The findings were consistent with the previously published reports [ 9 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…The characteristic peak of 1647 cm −1 indicated C=C and C=N stretching, and the peak of 1694 cm −1 demonstrated the stretching vibration of C=O. At the same time, the C–OH (alcohols and carboxylic acids) stretching peak appears at 1068 cm −1 [ 9 ]. The FTIR spectra of alginate, i.e., A ( Figure 1 ), showed characteristics of uronic acid at 987 cm −1 ; a wavenumber of 2965 cm −1 demonstrated CH 2 stretching of alginate, and simultaneously, wavenumbers from 3200 to 3600 cm −1 indicated OH stretching [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations